Working Motivation and Reward System Influenced Nurses’ Perception of Performance Mediated by Organizational Commitment - Kemala Rita Wahidi; Pamungkas, Winda Novita; Pamungkas, Idrus Jus’at (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Working motivation and reward system are infuencece factors on nurses’ perception on working Objectvie: The study aimed to examine the effect of working motivation and reward system on perception of nurse performance mediated organizational commitment. Method: A quantitative with causality explanatory was applied in this study. Sixty eight nurses were involved in this study. We analyze the data using the path analysis. Results: The results found that there is a significant effect between working motivation and reward system on perception of nurse performance mediated with organizational commitment at Tamumajaya Hospital. Conclusion: In conclusion showed that working motivation and reward system influenced the perception of nurses performance. Implication: The implication of this study showed that the optimal nursing care Could be achieved when the nurses have optimal performance